Designing Stable Deep‐Blue Thermally Activated Delayed Fluorescence Emitters through Controlling the Intrinsic Stability of Triplet Excitons (Advanced Optical Materials 12/2022). Issue 12 (20th June 2022) - Kang, Hosuk; Ihn, Soo‐Ghang; Kim, Inkoo; Chung, Yeon Sook; Jeon, Soon Ok; Sim, Myungsun; Kim, Joonghyuk; Lee, Hasup; Son, Youngmok; Son, Won‐Joon; Jang, Inkook; Kim, Dae Sin; et al.
Abstract : In article number 2102309, Soo‐Ghang Ihn, Won‐Joon Son, Jin Pyo Hong and co‐workers establish rational design principles for stable blue organic emitters with high chemical stability in triplet states. Repositioning the locus of triplet excitation away from the weakest bond via judicious molecular engineering reroutes the dissociation pathway to energetically less favorable and kinetically less probable conical intersection with a higher energy barrier. This research provides new insights into the excited‐state dissociation kinetics involved in molecular degradation under electrical stress.